A controlled study of hand function in nodal and erosive osteoarthritis. Issue 12 (December 1989) - Pattrick, M; Aldridge, S; Hamilton, E; Manhire, A; Doherty, M
Abstract : Hand function using a standardised test of activities of daily living was assessed in (a) 57 patients (53 female, four male; mean age 69 years) with established (that is, symptom onset greater than 10 years before) nodal generalised osteoarthritis (NGOA); (b) 10 patients (nine female, one male; mean age 70 years) with established erosive osteoarthritis (EOA); and (c) 52 matched controls (48 female, four male; mean age 71 years) with asymptomatic, clinically normal hands. Although significant differences between controls and patient groups were observed for individual tasks, only minor global impairment was seen, the worst function occurring in patients with EOA. There was no consistent correlation between tested aspects of hand function and extent of radiographic change assessed by summated graded score for separate osteoarthritic features in individual joints. In controls increasing age correlated with longer time to complete all tasks and weaker power grip; a similar, less pronounced correlation occurred in patients. Differences between controls and patients with NGOA were most apparent in younger subjects; in the elderly (greater than 80 years) hand function was essentially the same. This study shows good functional outcome for patients with NGOA, and suggests that the OA process is of little functional importance to the aging hand.